-4=-k/4

Simple and best practice solution for -4=-k/4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4=-k/4 equation:



-4=-k/4
We move all terms to the left:
-4-(-k/4)=0
We get rid of parentheses
k/4-4=0
We multiply all the terms by the denominator
k-4*4=0
We add all the numbers together, and all the variables
k-16=0
We move all terms containing k to the left, all other terms to the right
k=16

See similar equations:

| -u/4=-3 | | 6s+5(2)=102 | | -6b+2=-10-10b | | -h/1=-1 | | 24=-2(m | | 7x-(5x-8)-(-6x+1)=8×-9 | | j-4=9 | | q/3+11=12 | | 2^x7=16 | | 2+r=9 | | 21−3p=9 | | 7y=-10+5y | | 21−3p=921−3p=9 | | (2x-46)=(x+2) | | 6d=5+7d | | 699.8÷100=x | | 113=12k | | 8+m=2m | | -16-6c-12=12-8c | | -9t=7-10t | | 12=15(z-0.5) | | x-61=10(2x+3)-15 | | 9t=7−10 | | x−61=10(2x+3)−15 | | 4=n=-5+(-9) | | 5.36-7.1s=-3.49-7.6s | | 18.1h+7.55-17.39=19.9h+18.96 | | 2r+1=r | | 5m-5=-115 | | y+4/45-9=18 | | 1q7=13 | | x+.0.07x=8.35 |

Equations solver categories